2009
DOI: 10.1098/rspb.2009.1980
|View full text |Cite
|
Sign up to set email alerts
|

Selective biodegradation of keratin matrix in feather rachis reveals classic bioengineering

Abstract: Flight necessitates that the feather rachis is extremely tough and light. Yet, the crucial filamentous hierarchy of the rachis is unknown-study hindered by the tight chemical bonding between the filaments and matrix. We used novel microbial biodegradation to delineate the fibres of the rachidial cortex in situ. It revealed the thickest keratin filaments known to date (factor .10), approximately 6 mm thick, extending predominantly axially but with a small outer circumferential component. Near-periodic thickened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(121 citation statements)
references
References 44 publications
11
106
0
Order By: Relevance
“…Alternatively, if differences in orientation are subtle to begin with they might not be sufficiently different enough to diffract Busson et al's X-rays, or even show up on our modulus mapping; if the two innermost laminae are at similar orientations to the indenter tip despite being relatively different, they may also have been reported as a single lamina in the second indentation of C. olor. Further work is clearly needed to compare and contrast the two approaches as neither Lingham-Soliar et al [14], nor Busson et al [13] reported the location in the wing from where they sampled feathers. It is possible that the number of rachis laminae also varies along the wing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, if differences in orientation are subtle to begin with they might not be sufficiently different enough to diffract Busson et al's X-rays, or even show up on our modulus mapping; if the two innermost laminae are at similar orientations to the indenter tip despite being relatively different, they may also have been reported as a single lamina in the second indentation of C. olor. Further work is clearly needed to compare and contrast the two approaches as neither Lingham-Soliar et al [14], nor Busson et al [13] reported the location in the wing from where they sampled feathers. It is possible that the number of rachis laminae also varies along the wing.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2a,b does arguably show a thin lamina at the interface although it is more likely that none of the indentations landed directly on this proposed amorphous lamina and this is an artefact of the graphing software's interpolation algorithm. The scanning electron microscope (SEM) image presented by Lingham-Soliar [14] after microbial degradation does show Busson et al's [13] two 'feather' laminae but the nature of the degradation combined with their imaging method make it difficult to distinguish the amorphous lamina from the embedding substantia. It should be noted that we do not observe an amorphous lamina in between fibre laminae on any nano-indentation maps, nor in the CT scan, all of which show an abrupt transition from one fibrous lamina to another.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations